Gas storage valuation and hedging: A quantification of model risk - Patrick Hénaff; Ismail Laachir; Francesco Russo (International Journal of Financial Studies, 2018)
This paper focuses on the valuation and hedging of gas storage facilities, using a spot-based valuation framework coupled with a financial hedging strategy implemented with futures contracts. The contributions of this paper are two-fold. Firstly, we propose a model that unifies the dynamics of the futures curve and spot price, and accounts for the main stylized facts of the US natural gas market such as seasonality and the presence of price spikes in the spot market. Secondly, we evaluate the associated model risk, and show not only that the valuation is strongly dependent upon the dynamics of the spot price, but more importantly that the hedging strategy commonly used in the industry leaves the storage operator with significant residual price risk.
Keywords: C4; C5; C6; C8; G11; G13; G17; 330; energy markets; commodities; natural gas storage; model uncertainty